2012
DOI: 10.1002/jmv.23333
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of different HPV types in Turkish women with a normal Pap smear

Abstract: The age-specific human papillomavirus (HPV) seroprevalence and HPV type distribution in women with normal cervical cytology were studied. Cervical smear samples obtained using liquid-based smears from 582 clinically healthy women aged between 15 and 68 years from five centers from four different regions of Turkey, were studied between February 2010 and January 2011. Overall, 530 of the women with normal cytology were included and the samples were analyzed for the presence of HPV by AmpliTaq. Positive samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
7
22
1
6
Order By: Relevance
“…Therefore, the importance of cytological screening methods to detect lesions at an early phase of infection is clear. [3,7] In our study, HPV DNA-positivity was detected in 33.7% of the cases without cytological atypia. As a result, these patients were clinically monitored.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Therefore, the importance of cytological screening methods to detect lesions at an early phase of infection is clear. [3,7] In our study, HPV DNA-positivity was detected in 33.7% of the cases without cytological atypia. As a result, these patients were clinically monitored.…”
Section: Discussionsupporting
confidence: 50%
“…In other studies, HPV prevalence rates have ranged between 17.9% and 67.7%. [7,9,12,13] In the present study, HPV prevalence was reported as 41.1%. Our results are similar to those indicated by Kasap et al [13] from Turkey, and they are consistent with the world literature.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…As well as being the second cancer type that is the most common among women in the world, cervical cancer is the second most common reason for the cancer deaths [1][2][3][4] . According to the data revealed by Turkish Ministry of Health, while Araştırma Makalesi / Research Article cervical cancer incidence rate was 0.7/100000 in 1996, it increased up to 3.87/100000 in 2007 5 .…”
Section: Introductionmentioning
confidence: 99%